Loan products and credit scoring by commercial banks (India) - Itoo, R. A.; Selvarasu, A.; Filipe, J. A. (International Journal of Latest Trends in Finance and Economics Sciences, 2015)
This study describes the loan products offered by commercial banks and credit scoring techniques used for classifying risks and granting credit to applicants in India. Loan products offered by commercial banks are from several kinds, since housing loans, personal loans, business loans until education loans or vehicle loans, among many other types. All loan products are categorized either as secured or unsecured loans. Credit scoring techniques used for both secured and unsecured loans are broadly divided into two categories: Advanced Statistical Methods and Traditional Statistical Methods. Some methodologies are presented to discuss Indian situation and understand the different kind on retail loans offered by banks and the different credit scoring methods for personal finance used by commercial banks in India. Keywords ? Retail banks, Secured and Unsecured loans, Credit Scoring Techniques.